INCREASING THE EFFICIENCY OF ALLOCATION OF FINANCIAL RESOURCES OF INSURANCE COMPANIES (Лучшие интеллектуальные исследования, 2025)
Abstract . The article describes the emergence of insurance companies as a major source of investment in the economy. The analysis of the placement of financial resources by insurers and its effectiveness is carried out, and the issues of further expansion and optimization of the investment portfolio are studied. The expected results in the insurance sector through the introduction of these directions are also described.